Morphological Changes with growth in Liza cCarinata (Valenciennes) egg, larva and juvenile as distinguished from those of Liza Haematocheila (ScWegel) - Hassan, Anuar; Takita, Toru (Universiti Putra Malaysia Press, 1993)
The morphological changes in the egg, larval and juvenile stages of Liza carinata with growth were investigated in reared and wild specimens. L. carinata could be distinguished from L. haematocheila which is likely to spawn concurrently in time and space in the egg, larva, and juvenile stages. The eggs hatch within 45-102 h after fertilization in water of15-21 °C, corresponding to the temperature in the spawning ground. A newly-hatched larva averages 2.1 mm in total length. The anlage of the caudal fin appears in the larva of around 3.4 mm and the juvenile stage is attained at a length of 8.9 mm. L. haematocheila is distinguished fly its larger size in the egg and larval stages. The melanophores located on the top of the head and the rear end of the tail in L. carinata may also serve as distinguishing marks in the larval stages. The longer extension of the mid-lateral melanophore row in L. carinata distinguishes them in the juvenile stage. The characteristic dorsal ridge in L. carinata (which does not occur in L. haematocheila) appears after a total length of 30mm is reached.